Analisis Strategi Pemasaran Guna Memasuki Pasar Online Dalam Menghadapi Persaingan Selama Pandemi Covid-19 pada Bisnis Retail Toko ‘’Bintang’’ - Azril Fikri Hawari; Ety Dwi Susanti (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to determine the analysis of marketing strategies to enter the online market in the face of competition during the covid-19 pandemic. The type of research conducted is descriptive method. Data collection techniques in this study used observation, in-dept interview methods or in-depth interviews, and documentation. Sources of data from this study are the owner or owner, employee or employee, as well as consumers who have made transactions at the